A novel approach for the treatment of Jacob II and III fractures of the lateral humeral condyle in children: Percutaneous Kirschner wire fixation with ultrasound localization - Deng, Changzong; Shen, Zhien; Wang, Kai; Xu, Wenbin; Du, Weibin; Zhuang, Wei (Frontiers in Surgery, 2022)
This study investigated the therapeutic effect of percutaneous Kirschner wire fixation in children with Jacob II and III fractures of the lateral humeral condyle under ultrasound positioning. The clinical data of 28 children with Jacob II and III fractures of the lateral humeral condyle treated by percutaneous Kirschner wire fixation under ultrasound positioning in our hospital from January 2018 to April 2022 were retrospectively analyzed. We performed percutaneous Kirschner wire fixation under ultrasound positioning for all children and cast immobilization for 4-5 weeks. X-rays were reviewed on the first postoperative day to check the fracture reduction and Kirschner wire fixation. After 2 and 4 weeks, the X-rays were reviewed respectively to check the irritation of the needle tip, infection, and fracture healing. After confirming the fracture healing and callus formation, the plaster was removed and the Kirschner wire was pulled out. Rehabilitation exercises can be performed after removal to promote the recovery of elbow joint function. At the last follow-up, according to Flynn's evaluation criteria, 24 children were clinically rated as excellent, and 3 were clinically rated as good. At the last follow-up, according to the Mayo Elbow Functional Score Scale (MEPS), all 28 children had excellent scores. There was no significant difference in MEPS (99.80±0.39) score on the affected side and MEPS on the healthy side (99.92±0.17) (t=1.533, p>0.05). Percutaneous Kirschner wire fixation under ultrasound positioning has the advantages of portability, small incision and trauma, no radiation, good fixation, and reduced secondary injury, and is worthy of further clinical promotion.